Child health policy and practice in times of recession: Findings from Ireland - COYNE, IMELDA (My University, 2015)
Since 2009, Ireland has experienced a deep economic recession and despite some recent fiscal recovery, the effects of financial cutbacks continue to be felt. The recession did not impact on all individuals equally, however, and families with young children were particularly disadvantaged due to unemployment, housing problems and decreased income. This paper presents an overview of the key contribution of the public health nursing service as articulated in policy and research evidence over this time. While t he implementation of the service in recent years has been hampered by challenges arising as a consequence of this recession, there is some evidence that the public health nursing service continues to have strong commitment to their work with children and f amilies. Funding however, needs to be aligned with the explicit and stated commitments and this means ensuring the child health workforce is adequately resourced and funded to undertake this important work.
PUBLISHED
Keywords: Child health; policy; public health nursing; recession; services; community